Multiple sclerosis as a model to investigate SARS‐CoV‐2 effect on brain atrophy. (7th December 2022) - Rebsamen, Michael; Friedli, Christoph; Radojewski, Piotr; Diem, Lara; Chan, Andrew; Wiest, Roland; Salmen, Anke; Rummel, Christian; Hoepner, Robert
Abstract: Introduction: Data on structural brain changes after infection with SARS‐CoV‐2 is sparse. We postulate multiple sclerosis as a model to study the effects of SARS‐CoV‐2 on brain atrophy due to the unique availability of longitudinal imaging data in this patient group, enabling assessment of intraindividual brain atrophy rates. Methods: Global and regional cortical gray matter volumes were derived from structural MRIs using FreeSurfer. A linear model was fitted to the measures of the matching pre‐SARS‐CoV‐2 images with age as an explanatory variable. The residuals were used to determine whether the post‐SARS‐CoV‐2 volumes differed significantly from the baseline. Results: Fourteen RRMS patients with a total of 113 longitudinal magnetic resonance images were retrospectively analyzed. We found no acceleration of brain atrophy after infection with SARS‐CoV‐2 for global gray matter volume ( p = 0.17). However, on the regional level, parahippocampal gyri showed a tendency toward volume reduction ( p = 0.0076), suggesting accelerated atrophy during or after infection. Conclusions: Our results illustrate the opportunity of using longitudinal MRIs from existing MS registries to study brain changes associated with SARS‐CoV‐2 infections. We would like to address the global MS community with a call for action to use the available cohorts, reproduce the proposed analysis, and pool the results. Abstract : Does infection with SARS‐CoV‐2 in MS patients lead to a change in brain atrophy? MS is an ideal model disease to study the potential effects of infection with SARS‐CoV‐2 on brain atrophy, as longitudinal clinical and imaging data are abundant. In this proof‐of‐principle study, we found no evidence of accelerated atrophy of global gray matter volume but accelerated atrophy in the parahippocampal gyri.